2011
DOI: 10.1007/s13142-011-0091-6
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain on the global stage: what next?

Abstract: In this essay, we describe two recent developments in global public health efforts in the chronic pain field and use the example of musculoskeletal pain to explore some of the implications arising from these developments. The first is the recognition of chronic pain as a condition in its own right, which has been the impetus for several national and one recent international pain summits that have translated that into a call for recognition, rights and resources for people with pain. The other development is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…4 Good pain management services are essential for improving patient outcomes and quality of life. 5,6 Developing and applying effective strategies for managing pain is crucial 7 , highlighting the significant impact of pain and the importance of addressing it thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…4 Good pain management services are essential for improving patient outcomes and quality of life. 5,6 Developing and applying effective strategies for managing pain is crucial 7 , highlighting the significant impact of pain and the importance of addressing it thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that this is due to chronic pain often being considered as a symptom of something rather than a specific condition in its own right [17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite being highly prevalent, placing a huge burden on individuals’ lives and resulting in extensive costs to the economy, chronic pain has not been afforded the same priority as many other chronic conditions. It has been suggested that this is due to chronic pain often being considered as a symptom of something rather than a specific condition in its own right [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This special issue concludes with an essay by Blyth and Hoy [18] that addresses global public health issues in the treatment of a common chronic pain condition-musculoskeletal pain. The authors note that there is growing agreement that pain needs to be considered a health condition in its own right and highlight the implications of this for health policy in the areas of pain prevention and treatment.…”
mentioning
confidence: 99%